Passive Design Strategies for Improving Natural Ventilation in a Tropical Corner House - Doddy Yuono; Yunita Ardianti Sabtalistia (Asosiasi Dosen Muda Indonesia, 2026)
Natural ventilation is an important passive strategy for improving thermal conditions and reducing dependence on mechanical cooling in tropical houses. Corner houses offer greater ventilation potential due to their multiple exposed façades, although inappropriate spatial and opening configurations may limit airflow. Objective: This study develops a corner-house design model to improve natural ventilation based on the environmental evaluation of an existing residential building. Methodology: A descriptive qualitative and quantitative approach was applied to a type 27/60 corner house in Forest Hill Housing. Literature and SNI standards were reviewed, while air temperature, relative humidity, and air velocity were measured using a hygro-thermometer and an anemometer. The results were evaluated to identify ventilation problems and formulate design solutions. Findings: Most indoor spaces recorded air velocities of only 0–0.1 m/s, while the carport and terrace reached 1.5 and 1.4 m/s at midday. Indoor temperatures reached 30.6°C in the drying area and 30.5°C in the dining room, indicating that available outdoor airflow was not effectively distributed indoors. The proposed redesign therefore integrates additional openings, cross and stack ventilation, operable skylights, an innercourt, increased ceiling height, spatial reconfiguration, and solar shading. Implications: The proposed strategies provide practical design considerations for improving natural ventilation in tropical corner houses and potentially reducing reliance on mechanical cooling. Originality: This study translates field-measured environmental deficiencies into an integrated passive redesign that combines multiple exposed façades, horizontal and vertical airflow strategies, spatial reconfiguration, and solar control.